Regulation of the metastatic cell phenotype by sialylated glycans - Schultz, Matthew J. (2012)
Tumor cells exhibit striking changes in cell surface glycosylation as a consequence of dysregulated glycosyltransferases and glycosidases. In particular, an increase in the expression of certain sialylated glycans is a prominent feature of many transformed cells. Altered sialylation has long been associated with metastatic cell behaviors including invasion and enhanced cell survival; however, there is limited information regarding the molecular details of how distinct sialylated structures or sialylated carrier proteins regulate cell signaling to control responses such as adhesion/migration or resistance to specific apoptotic pathways. The goal of this review is to highlight selected examples of sialylated glycans for which there is some knowledge of molecular mechanisms linking aberrant sialylation to critical processes involved in metastasis.